Slow pathway modification in patients presenting with only two consecutive AV nodal echo beats. Issue 2 (February 2017) - Wegner, Felix K.; Silvano, Maria; Bögeholz, Nils; Leitz, Patrick R.; Frommeyer, Gerrit; Dechering, Dirk G.; Zellerhoff, Stephan; Kochhäuser, Simon; Lange, Philipp S.; Köbe, Julia; Wasmer, Kristina; Mönnig, Gerold; et al.
Abstract: Background: Slow pathway modification (SPM) is the therapy of choice for AV-nodal reentry tachycardia (AVNRT). When AVNRT is not inducible, empirical ablation can be considered, however, the outcome in patients with two AV nodal echo beats (AVNEBs) is unknown. Methods: Out of a population of 3003 patients who underwent slow pathway modification at our institution between 1993 and 2013, we retrospectively included 32 patients with a history of symptomatic tachycardia, lack of paroxysmal supraventricular tachycardia (pSVT) inducibility but occurrence of two AVNEBs. Results: pSVT documentation by electrocardiography (ECG) was present in 20 patients. The procedural endpoint was inducibility of less than two AVNEBs. This was reached in 31 (97%) patients. Long-term success was assessed by a telephone questionnaire (follow-up time 63 ± 9 months). A total 94% of the patients benefited from the procedure (59% freedom from symptoms; 34% improvement in symptoms). Among those patients in whom ECG documentation was not present, 100% benefited (58% freedom from symptoms, 42% improvement). Conclusion: This is the first collective analysis of a group of patients presenting with symptoms of pSVT and inducibility of only two AVNEBs. Procedural success and clinical long-term follow-up were in the range of the reported success rates of slow pathway modification of inducible AVNRT, independent of whether ECG documentation was present. Thus, SPM is a safe and effective therapy in patients with two AVNEBs.